2021
DOI: 10.31219/osf.io/b8x6w
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sulfur in kukersite shale oil: its distribution in shale oil fractions and the effect of gaseous environment

Abstract: In this article, we present data on the distribution of sulfur in Estonian kukersite shale oil. It was found that the highest concentration of sulfur is present in the fractions boiling between about 150 and 190°C. Also, we studied the effect of N2, N2/steam, CO2, and CO2/steam environments on the concentrations of some sulfur compounds in shale oil. The results show that thiophenic compounds comprise most of the sulfur compounds in crude kukersite shale oil. Furthermore, CO2 increased the concentration of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The data used for the analysis in this article was part of a larger study to investigate the properties of kukersite shale oil. The elemental composition data and additional properties of the samples studied here were given in the earlier articles by Järvik et al [12], Mozzafari et al [13], and Järvik and Oja [14], the data can also be found from the Open Science Framework repository (https://osf.io/3q5ur).…”
Section: Elemental Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The data used for the analysis in this article was part of a larger study to investigate the properties of kukersite shale oil. The elemental composition data and additional properties of the samples studied here were given in the earlier articles by Järvik et al [12], Mozzafari et al [13], and Järvik and Oja [14], the data can also be found from the Open Science Framework repository (https://osf.io/3q5ur).…”
Section: Elemental Analysismentioning
confidence: 99%
“…Past studies have determined that the sulfur compounds in kukersite oil are mostly alkylthiophenes and thioesters, although some mercaptans and disulfides are also present [13,30,32].…”
Section: Sulfur Compoundsmentioning
confidence: 99%
“…Past studies have determined that the sulfur compounds in kukersite oil are mostly alkylthiophenes and thioesters, although some mercaptans and disulfides are also present [13], [30], [31]. This type of sulfur distribution is different from that normally seen with conventional petroleum.…”
Section: Sulfur Compoundsmentioning
confidence: 99%
“…Even Jordanian El Lajjun shale oil, which is known for its high sulfur content, shows a decrease in sulfur content in the heavier fractions [26]. A more detailed analysis of the sulfur compounds in kukersite shale oil is given in one of our other articles [13].…”
Section: Sulfur Compoundsmentioning
confidence: 99%
“…H 2 S release from coal during pyrolysis in an N 2 inert atmosphere was detected by Chen et al [55], while Yani et al [56] also detected the release of H 2 S and SO 2 gases from pyrolized lignite samples. Mozaffari et al [57] showed the release of sulfur compounds in Estonian kukersite shale oil obtained using pyrolysis at temperatures lower than 520 • C; in particular, they demonstrated that the presence of steam during pyrolysis led to an increase in H 2 S release.…”
mentioning
confidence: 99%